Pengembangan Desa Wisata Candirejo sebagai Pariwisata Berkelanjutan - Subarkah, Johan; Amelia, Viona (Jayapangus Press, 2023)
Candirejo Tourism Village is one of the villages that is well aware of its potential and packaged as one of the supporting attractions in the Borobudur Temple area. After its development as a tourist village, an analysis is needed to see the impacts caused by tourism activities, both positive and negative impacts. The impact of tourism requires some monitoring to protect the community's right to obtain welfare, as well as to ensure the long-term viability of tourism products. This research was conducted with the aim of analyzing the development of the tourism sector in the Candirejo Tourism Village with economic, socio-cultural, environmental aspects and its impact on the local community. This research uses a descriptive qualitative research method using an depth interview method and is supported through various related literature sources. The purposive sampling technique was used to determine respondents or sources, namely the management of the Candirejo Tourism Village Cooperative, which plays a role in tourism development in Candirejo Tourism Village. The results of the research and discussion show that the life of the Candirejo tourism village community has improved economically, has increased social interaction with tourists or visitors, and the natural environment is still maintained, because of high public awareness supported by the behaviour of tourists who are aware of environmental cleanliness. The conclusion of this research is that tourism activities that take place in Candirejo tourism village provide more positive developments in the aspects of the socio-cultural life of the community, economic improvement, and environmental sustainability.